Depositional Environments and History of Late Quaternary Sediments in Hudson Strait and Ungava Bay: Further Evidence from Seismic and Biostratigraphic Data - MacLean, Brian; Vilks, Gustav; Deonarine, Bhan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTRegional ship-borne investigations of seafloor sediments provide further information on late Quaternary depositional environments and history in the Hudson Strait-Ungava Bay region. Greatest sediment thicknesses, up to 130 m, occur in the large basin in eastern Hudson Strait and in the western Hudson Strait basin north of Charles Island. Significant deposits are also present in basins southwest of Charles Island, along the south central part of the Strait, and in the southern part of Ungava Bay. Glacial drift deposits are widespread, but glaciomarine and postglacial sediments mainly occur in the basinal areas, with glaciomarine sediments generally predominating. Glaciomarine sediments are laterally transitional to glacial drift in the south central part of the Strait, and at many other basin margins. AMS dating of the deepest shells found within three cores from the glaciomarine sequences in the Wakeham Bay-Baie Héricart region of south central Hudson Strait yielded ages of 8390 ± 70,8420 ± 80, and 8520 ± 80 BP. Sequences underlying the dated intervals may contain time equivalents of glaciomarine sediments 1000-2000 years older found onshore in the Deception Bay area by Gray, Bruneau, and others.